Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/21582440221095003
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Principal’s Authentic Leadership Impact on the Organizational Citizenship Behavior and Well-Being of Teachers

Abstract: As teacher well-being is impacted by the leadership ability of school management, which helps establish trust and cooperation among the teaching faculty, it is an important subject of research. Therefore, this study aims to explore how the authentic leadership of school principals impacts (1) the teacher-school relationship (based on organizational trust, organizational identification, and organizational commitment), and (2) teachers’ organizational citizenship behavior. In addition, mediating effects of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…In the field of education, leadership behaviour is one of the factors that have a significant relationship with teacher OCB (Febriantina et al, 2021;Kumar et al, 2022;Shie & Chang, 2022;Shofiyuddin, 2021). However, research on the relationship between servant leadership and teacher OCB was found to be lacking (Shamsuddin et al, 2020), despite the fact that this leadership style was found to be preferred by teachers and more effective than authoritative leadership due to the better use of the leader's power (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of education, leadership behaviour is one of the factors that have a significant relationship with teacher OCB (Febriantina et al, 2021;Kumar et al, 2022;Shie & Chang, 2022;Shofiyuddin, 2021). However, research on the relationship between servant leadership and teacher OCB was found to be lacking (Shamsuddin et al, 2020), despite the fact that this leadership style was found to be preferred by teachers and more effective than authoritative leadership due to the better use of the leader's power (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To be trusted we must be honest, faithful in supporting others, keep believing in ourselves, and do what we should do (Stephen P. Robbins, 1994). Integrity is included in one of the principles of authentic leadership, where this leadership describes a positive leadership style as a style that focuses on integrity, honesty, and high moral values (Shie & Chang, 2022). Authentic leadership according to Iszatt-White & Kempster, (2019) is a behavioral style of leaders creating and enhancing positive psychological and moral competencies to further develop self-awareness, internalized moral perspective, balanced information processing, and relational transparency.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have investigated the impact of different leadership styles on organizational commitment and trust, with a particular emphasis on the crucial role of transformational leadership in fostering trust and increasing commitment levels among employees (Liggans et al, 2019). Transformational leaders who demonstrate authenticity and inspire trust are better positioned to cultivate a culture of commitment and engagement within the organization (Shie & Chang, 2022).…”
Section: The Symbiotic Relationship Of Commitment and Trustmentioning
confidence: 99%